Semi-empirical calculations of the vibrational frequency of carbon monoxide adsorbed on noble metal single-crystal surfaces - Paredes Olivera, P. A. (1993)
In this work we perform a theoretical analysis of the shift of the observed IR reflection—absorption spectroscopy (IRRAS) band of CO adsorbed on Pt(111), Rh(111) and Pt(100) single crystals as a function of both the degree of CO surface coverage and the electric potential applied at either the metal—vacuum or the metal—solution interface. The wavefunctions obtained using a modified extended Hückel molecular orbital (EHMO) method are used to predict the vibrational frequency data. The Pt(110), Rh(111) and Pt(111) single crystals are modelled by bilayer clusters of 25 and 22 atoms respectively. A theoretical description of the observed IRRAS shift is analysed by means of a population analysis of CO molecular orbitals, which confirms the donation—back-donation model.